Direct Assessment of the Toxicity of Molybdenum Disulfide Atomically Thin Film and Microparticles via Cytotoxicity and Patch Testing. Issue 12 (22nd January 2018) - Chen, Weibing; Qi, Wenjin; Lu, Wei; Chaudhury, Nikhil Roy; Yuan, Jiangtan; Qin, Lidong; Lou, Jun
Abstract: The low toxicity of molybdenum disulfide (MoS2 ) atomically thin film and microparticles is confirmed via cytotoxicity and patch testing in this report. The toxicity of MoS2 thin film and microparticles is extensively studied but is still inconclusive due to potential organic contamination in the preparations of samples. Such contamination is avoided here through preparing MoS2 atomically thin film via direct sulfurization of molybdenum thin film on quartz plate, which permits a direct assessment of its toxicity without any contamination. Six different types of cells, including normal, cancer, and immortal cells, are cultured in the media containing MoS2 thin film on quartz plates or dispersed MoS2 microparticles and their viability is evaluated with respect to the concentrations of samples. Detached thin films from the quartz plates are also investigated to estimate the toxicity of dispersed MoS2 in biological media. Allergy testing on skin of guinea pigs is also conducted to understand their effect on animal skins. By avoiding possible organic contamination, the low toxicity of MoS2 atomically thin film and microparticles to cells and animal skins paves the way for its applications in flexible biosensing/bioimaging devices and biocompatible coatings. Abstract : Toxicity of few‐layer MoS2, one of the thinnest semiconductors which can be potentially employed in the microscale in vivo biosensors, is evaluated by preparing samples via direct sulfurization of Mo thin film on biofriendly quartz plates to avoid the influence of organic chemical residuals by other preparation methods. The results confirm the low toxicity of these very thin nanomaterials.